Peningkatan Kecakapan Bahasa Inggris Santri di Masa Pasca Covid-19 melalui Program Pengajaran TOEFL di SMA Berbasis Pesantren - Abdur Rofik; Christina Christina (Universitas Mathla'ul Anwar Banten, 2021)
IMPROVING SANTRI’S ENGLISH SKILLS IN THE POST-COVID-19 PERIOD THROUGH THE TOEFL TEACHING PROGRAM IN PESANTREN-BASED SMA. This Community Service (PKM) aims to improve English skills through the TOEFL teaching program for santri of PPTQ Al Asy'ariyyah Kalibeber, Wonosobo. The santri also received formal education at SMA Takhassus Alqur'an Wonosobo. One of the factors underlies this PKM is that these santri have never received TOEFL material. In addition, they also do not know what skills are tested on the TOEFL. The methods used in this PKM are (1) Preparation (by conducting a needs analysis through FGD with the English teachers), (2) Providing material (using lecture, presentation, question and answer methods, as well as practice questions and discussions), and ( 3) evaluating the success of PKM (by holding a TOEFL-Like Test). Based on the results of the PKM evaluation, the team concluded that this service activity reached the standard according to the specified target because it was able to provide participants with an understanding of the skills tested in the TOEFL-Like Test. In addition, the first experience of 27 santri in the TOEFL-Like Test with a mean score of 376.70 from those who initially did not have knowledge of the TOEFL was a pretty good achievement. The evaluation results also showed that of the three skills tested, the students had weaknesses in structure and written expression, and the best in reading skills, while listening skills were in expression of structural and writing skills as well as reading skills.